Semarak Bisnis Ritel Di Kota Padang: Perubahan Gaya Hidup Tahun 1990-an - Ririn Pradita Tania; Yelda Syafrina (Jurnal Kronologi, 2023)
ABSTRACT This study examines the Lively Retail Business in the City of Padang: Changes in the Lifestyle of City People in the 1990s. The purpose of this research is first to reveal the early history of the emergence of the retail business until it reaches the very rapid development it is today. The second explains the changes in the lifestyle of the people of Padang City in the 1990s as an important factor in the development of the retail business in the city of Padang. This study uses historical research methods covering four stages, namely heuristics (searching for and collecting data), source criticism, interpretation (interpreting or giving meaning to historical facts or evidence) and historiography (history writing). The primary source was obtained from the Perindagtanben Office in the form of documents. The results of the study show that the initial appearance of the retail business in the city of Padang came from the initiative of local entrepreneurs who saw significant opportunities in this business. In addition, this study also found that in the early 1990s the people of Padang were very familiar with modern retail. Keywords : Retail, Lifestyle Changes, Padang City ABSTRAK Penelitian ini mengkaji tentang Semarak Bisnis Ritel Di Kota Padang: Perubahan Gaya Hidup Masyarakat Kota Tahun 1996-an. Tujuan penelitian ini pertama yaitu ingin mengungkap sejarah awal kemunculan bisnis ritel hingga mencapai perkembangan yang sangat pesat seperti sekarang. Kedua menjelaskan perubahan gaya hidup masyarakat Kota Padang tahun 1990-an sebagai faktor penting berkembangnya bisnis ritel di kota Kota Padang. Penelitian ini menggunakan metode penelitian sejarah meliputi empat tahap yaitu heuristik (mencari dan mengumpulkan data), kritik sumber, interpretasi (menafsirkan atau memberi makna fakta-fakta atau bukti sejarah) dan historiografi (penulisan sejarah). Sumber primer didapatkan dari Dinas Perindagtanben berupa dokumen. Hasil penelitian menunjukan bahwa kemunculan awal bisnis ritel di kota Padang berasal dari inisiatif pengusaha lokal yang melihat peluang dari usaha ini cukup signifikan. Selain itu penelitian ini juga menemukan bahwa di awal tahun 1990-an masyarakat kota Padang sudah sangat familiar dengan ritel modern. Kata Kunci : Ritel, Perubahan Gaya Hidup, Kota Padang